Encouraging Unity in Diversity via Marriage: The Stories of Interfaith Couples and Their Negotiations with State Obligations in Same-Faith Marriages - Syaifuddin, Muhammad Irfan; Syamsiyatun, Siti; Dhewayani, Jeanny (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2025)
This research aims to explore how interfaith couples experience encounter government intervention in supporting same-faith marriage according to article 2 Marriage Law number 1 of 1974. The study employs a qualitative approach, utilizing in-depth interviews, direct observations, and an analysis of marriage documents from six interfaith couples located in Surakarta. The participants were specifically chosen as those who had their interfaith marriages acknowledged by the Surakarta District Court and obtained a marriage certificate from the Surakarta City Population and Civil Registry Office. The gathered data were subjected to analysis through the lens of Stella Ting-Toomey’s identity negotiation theory, which highlights four essential skills individuals must possess to effectively navigate differences: self-awareness, awareness of others, adaptability, and empathy. The findings indicate that each interfaith couple in Surakarta engages in negotiation at three key stages: pre-marital negotiations, negotiations occurring during the marriage, and post-marital negotiations. Among the six couples studied, there was no uniformity in the negotiation patterns relating to the governmental-religious obligation that typically favours one-religion marriage. Three distinct negotiation patterns emerged: fully adhering to a state-sanctioned religious marriage, opting for a religious marriage instead of a state marriage, and preferring a state marriage over a religious one.